Furin is involved in uterine activation for labor. Issue 5 (17th April 2021) - Zhang, Youyi; Xu, Chen; Tang, Zhengshan; Guo, Dewei; Yao, Ruojin; Zhao, Huina; Chen, Zixi; Ni, Xin
Abstract: The uterus undergoes distinct molecular and functional changes during pregnancy and parturition. These processes are associated with the dramatic changes in various proteins. Given that the maturation and activation of many proteins require proteolytic processing by proprotein convertases (PCs), we sought to explore the role of PCs in uterine activation for labor. First, we found that furin was the most dramatically increased PC member in myometrial tissues from the pregnant women after onset of labor at term. Using the model of cultured human myometrial smooth muscle cells (HMSMCs), we showed that furin inhibitor CMK, D6R treatment and furin siRNA transfection suppressed contractility. Inhibition of furin activity or interfering furin expression decreased connexin 43 (CX43), prostaglandin (PG) endoperoxide synthase‐2 (COX‐2) and PGF2α receptor (FP) expression and NF‐κB activation. In mouse model, administration of furin inhibitors prolonged gestational length. However, D6R treatment did not affect RU38486‐ and lipopolysaccharides (LPS)‐induced preterm birth. Furthermore, D6R and furin siRNA treatment reduced the release of soluble form of tumor necrosis factor (TNF)‐related weak inducer of apoptosis (TWEAK), while furin overexpression led to an increase in soluble TWEAK release in cultured HMSMCs. D6R treatment decreased TWEAK level in blood of pregnant mice. TWEAK treatment promoted contractility and NF‐κB activation, while TWEAK receptor fibroblast growth factor‐inducible 14 (FN14) antagonist treatment inhibited contractility and NF‐κB activation in HMSMCs. In pregnant mice, administration of FN14 antagonist prolonged gestational length. Our data suggest that furin can act as a stimulator for uterine activation for labor at term. TWEAK is one of the potential substrates which mediate furin regulation of parturition initiation.